AN OPPORTUNITIES AND CHALLENGES OF THE INDONESIAN FILM INDUSTRY BASED ON DIGITAL PROMOTION TRANSFORMATION - Retno Indriasari; K.P.Suharyono S.Hadiningrat; Febri Pramudya Wardani (Yayasan Inspirasi Merah Putih Indonesia, 2025)
The rapid advancement of Information and Communication Technology (ICT) has significantly reshaped various aspects of life, requiring swift mitigation, adaptation, and responsive action to avoid being left behind. In the film industry, this shift not only demands enhanced creative and futuristic performance but also the integration of digital technology-based innovation. Accelerating digital literacy is crucial to overcoming disruption by developing both human resources within the film ecosystem and delivering high-quality film products that satisfy audiences. In this regard, digital promotion has become essential for film companies to stay competitive and avoid the risk of decline due to an inability to adapt effectively. The film business is highly dynamic, with success largely influenced by the quality of films that can both entertain and meet audience expectations, making alignment between customer needs and film content a critical factor. This research employs a qualitative descriptive design using SWOT analysis to identify the industry's current position and determine suitable strategies for transitioning from traditional to digital promotion. The study aims to explore and describe the opportunities and challenges the film industry faces in transforming its promotional practices to increase customer engagement and satisfaction in the digital age. Findings show that digital promotion transformation has opened significant opportunities for Indonesia’s film industry, including global access through streaming platforms, real-time engagement with audiences via social media, and data-driven decision-making. Nevertheless, challenges such as increasing competition, technological dependency, copyright issues, and evolving consumer behavior remain. With its rich cultural narratives, the Indonesian film industry holds great potential to reach international markets if it can utilize digital technology effectively. Therefore, a deep understanding of market dynamics and adaptability is key to success. The SWOT analysis highlights strengths such as content creativity, government support, and improved internet access; weaknesses including limited resources, low digital literacy, and variable production quality; opportunities such as the growth of streaming services, influencer collaborations, and global content reach; and threats like global competition, piracy, and changing viewer preferences. Based on this, several recommendations are proposed, including strengthening digital marketing strategies, enhancing content quality, offering training and capacity development, promoting stakeholder collaboration, improving copyright protection, and adapting to shifting consumer behavior in order to ensure a sustainable and competitive film industry in the digital era.